Exploring Japanese Cultural Representation In Anime: A Linguistic Analysis Of One-Piece Wano Kuni Arc - Nona Dince, Maria; Mujani, Sahril; Mashuri, Mashuri (Alinea: Jurnal Bahasa, Sastra dan Pengajaran, 2024)
This research aims to identify the use of the traditional Japanese language in the popular anime One Piece, especially the Wano Kuni arc by Eiichiro Oda. The research method used is descriptive analysis, which aims to examine the use of Japanese honorifics, ancient samurai terms (samurai terminology), and dialect in dialogue in the Wano Kuni arc. Data collection will be carried out by direct observation and note-taking techniques with an emphasis on sociolinguistic elements. Based on the results, there are several sociolinguistic elements that Eiichiro Oda uses to convey the story in his anime, namely, traditional Japanese honorifics, dialects, speech patterns, and samurai terminology. This shows that the plot of Wano Kuni presents the use of the traditional Japanese language accurately and depicts the cultural hierarchy and traditional values of Japanese society.